FINANCIAL PERFORMANCE TREND ANALYSIS BASED ON LIQUIDITY, SOLVABILITY, AND PROFITABILITY RATIOS AT PT BUKIT ASAM TBK 2021–2025 - Three Daughter Daeli; Amanda Olivia; Ani Rahmawati; Anggun Ananda (Journal Informatic, Education and Management (JIEM), 2026)
The purpose of this study is to examine patterns in the financial performance of PT Bukit Asam Tbk (PTBA) for the 2021–2025 period based on liquidity, solvency, and profitability ratios. PTBA is one of the largest coal mining companies in Indonesia whose performance is influenced by global coal price dynamics and economic conditions. This study uses a descriptive quantitative method using PT Bukit Asam Tbk's financial report data for 2021–2025 obtained from the company's annual report as secondary data. The analysis is carried out by calculating liquidity ratios consisting of the Current Ratio, Quick Ratio, and Cash Ratio; solvency ratios including the Debt to Asset Ratio, Debt to Equity Ratio, and Long-Term Debt to Equity Ratio; and profitability ratios including Gross Profit Margin, Net Profit Margin, Return on Assets, and Return on Equity. The results show that the liquidity ratio experienced a downward trend during the study period, indicating increasing pressure on the company's working capital management. The solvency ratio showed an upward trend, reflecting the increasing use of debt in the company's funding structure, although still within relatively safe limits. Meanwhile, the profitability ratio experienced a significant decline due to the normalization of global coal prices and the company's increasing operating expenses. Overall, PT Bukit Asam Tbk experienced two performance phases: a growth phase in 2021–2022 and a consolidation phase in 2023–2025. The results of this study are expected to provide consideration for company management, investors, and researchers in assessing the company's financial condition and future prospects.